Reduction of heavy metal movement in soil contaminated with diesel using Corncob-Biochar - Chaiyaraksa, Chompoonut; Phumcharoen, Ketklao (My University, 2021)
This research aimed to study the effect of biochar on the stability of Mn, Cd, and Pb in soil contaminated with diesel. The clay with pH 6.80, medium in organic matter (OM), high in cation exchange capacity (CEC), low in phosphate and salinity was from Bang Rong Subdistrict, Klong Khuen District, Chachoengsao Province (N13˚50’32.1252” E101˚ 9’5.6808”). The metal content is in the standard for use in agriculture. The soil sample was prepared to contain Mn, Pb, and Cd at 2,000 mg/kg, 550 mg/kg, and 50 mg/kg, respectively. The biochar from corncob was neutral, low in CEC, high in conductivity and OM. The surface area, pore-volume, pore radius, acid neutralization capability, and the pH at the point of zero charges (pHPZC) were 61.189 sq. m/g, 0.088 mL/g, 13.664 Angstrom, 1,000 meq/kg, and 6.80, respectively. Five percent of biochar was mixed to the soil containing 2% and 5% of diesel at room temperature for 2, 4, and 8 weeks before extraction with diethylenetriaminepentaacetic acid (DTPA) and sequential extraction. The results indicated that the higher the amount of diesel in soil, the slower the metal movement. Biochar could retard the mobility of Mn, Pb, and Cd in the soil sample. Five percent of biochar was not enough to decrease the metal mobility in soil contaminated with diesel 5%. The amount of extracted heavy metals increased with the more extended mixing period. The addition of biochar to the soil sample could change metals from unstable to stable forms.
Keywords: Corncob-biochar; Diesel; Heavy metals; Mobility retardation; Soil